The Influence of Fetch on the Holocene Thermal Structure of Hidden Lake, Glacier National Park - Stone, Jeffery R.; Saros, Jasmine E.; Spanbauer, Trisha L. (Frontiers in Earth Science, 2019)
We use three-dimensional modeling of the basin of Hidden Lake, Montana, to assess the influence of effective fetch on diatom-inferred changes in mixing depths throughout the Holocene. The basin of Hidden Lake is characterized by a complex morphometry; for example, three-dimensional modeling of the lake basin indicates that a decrease in lake level of 2 m would result in complete isolation of the deepest part of the lake basin from the rest of the lake. Our model suggests that small changes in the lake surface elevation at Hidden Lake would produce threshold-like responses in effective fetch, which in turn would have a profound influence on average lake mixing depth. The present-day planktic diatom community of Hidden Lake is comprised of three species. Neo-ecological experiments revealed the effect of mixing depth and nutrient levels on growth rates of these species. A sediment core collected from the deepest part of the lake basin and spanning the last 8,640 years was analyzed for diatoms. Here we show how changes in fetch through the Holocene explain changes in the dominant planktic diatom species by modification of the thermal structure of Hidden Lake. Additionally, the timing of diatom-inferred changes in effective moisture and thermal structure from Hidden Lake were compared to late Holocene patterns reconstructed from other regional lake records. Between 8.64 – 7.61 ka the diatom record from Hidden Lake suggests that the lake was deep and fresh, although somewhat lower than the modern lake. After 7.61 ka, water levels rose, expanding the available benthic diatom habitat. Between 6.18 and 4.13 ka, lake level declined and seasonal stratification was enhanced. After 1.4 ka, the lake became deeper and less stratified in response to the effects of enhanced fetch. We argue that changes in effective fetch may play an important, and underexplored, role in planktic diatom community structure over longer time scales and should be more broadly considered in paleolimnological studies.